The influence of risk management committee characteristics on the performance of non-financial listed firms in Malaysia from the perspective of agency and resource dependency theories - Boudiab, Mourad (2020)
The purpose of this study is to examine the relationship between risk management committee (RMC) characteristics and firm performance measured by (Tobin's q [TOBSQ], return on equity [ROE], return on asset [ROA], and earnings per share [EPS]) of listed firms in Malaysia from the year 2016 to 2018 using agency and resource dependency theories. Data were collected from the DataStream (Thomson DataStream) and annual reports of 646 sampled firms (1801 firm-year observations). To test the hypotheses developed in this study, the Panel Corrected Standard Errors (PCSEs) regression was used. Overall, the findings indicate that RMC size, RMC qualification, and RMC gender have a significant positive effect on firm performance. The study also finds that RMC overlap and RMC training are associated with high firm performance (Tobin's q, ROE, ROA, and EPS). However, the results indicate that separate RMC and RMC independent have significant negative relation with firm performance (Tobin's q, ROE, ROA, and EPS). While RMC interlocking shows significant negative association with firm performance (ROE, ROA, and EPS). RMC diligence has a significant negative effect on Tobin's q. Consequently, the result of this study portrays the influence of RMC characteristics in the Malaysian non-financial institutions. In addition, the findings of this study offer meaning full insight to the regulators and policymakers of corporate governance (CG) reforms in Malaysia to review and strengthen the existing CG code where necessary. Besides, this study has also provided an important intuition to the shareholders, financial analysts, corporate managers, and the academic communities to further understand the impact of RMC characteristics on firm performance.